2001
DOI: 10.1046/j.1365-294x.2001.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Spawning success in Atlantic salmon (Salmo salar L.): a long‐term DNA profiling‐based study conducted in a natural stream

Abstract: Spawning success of Atlantic salmon (Salmo salar L.) was investigated, under near-natural conditions, in the Girnock Burn, an 8-km long tributary of the River Dee in Scotland. Employing minisatellite-based DNA profiling, mating outcomes were resolved over three spawning seasons by assigning parentage to progeny samples removed from spawning nests ('redds'). While individual spawning patterns differed markedly, consistent trends were present over the 3 years studied. Multiple spawning was found to be prevalent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 61 publications
(90 reference statements)
6
76
0
Order By: Relevance
“…Nevertheless, the reasoning implies that parr reproductive contribution increases N e by reducing the variance in (male) individual reproductive success. Empirical investigations have often applied theory for discrete generations, through the influence of mature parr on sex bias (e.g., L'Abée-Lund 1989; Consuegra et al 2005) or individual reproductive success in a single breeding season (e.g., Martinez et al 2000;Taggart et al 2001). Both approaches may not correctly reflect processes in agestructured populations with overlapping generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the reasoning implies that parr reproductive contribution increases N e by reducing the variance in (male) individual reproductive success. Empirical investigations have often applied theory for discrete generations, through the influence of mature parr on sex bias (e.g., L'Abée-Lund 1989; Consuegra et al 2005) or individual reproductive success in a single breeding season (e.g., Martinez et al 2000;Taggart et al 2001). Both approaches may not correctly reflect processes in agestructured populations with overlapping generations.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to account for the influence of male parr maturation on age-specific reproductive contribution of males as follows. In the absence of data for the rivers, we used empirical values from observations under natural ( Jordan and Youngson 1992;Martinez et al 2000;Garant et al 2001;Taggart et al 2001) and experimental conditions (Hutchings and Myers 1988;Moran et al 1996;Thomaz et al 1997;Garcia-Vazquez et al 2001;Hutchings 2001, 2002). These studies suggest that mature male parr account for $30% of the fertilizations in direct competition with anadromous fish, over a wide range of operational sex ratios.…”
mentioning
confidence: 99%
“…the portion of eggs resulting from one spawning act also called an egg pocket) or several nests spawned in successive pits (Ottaway et al, 1981;Crisp and Carling, 1989). Normally the female will spread her offspring in several redds within the river (Webb and Hawkins, 1989;Baglinière et al, 1990;Barlaup et al, 1994;Garant et al, 2001;Taggart et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Salmon that are holding position prior to spawning are likely maintaining a position near their eventual spawning site and not necessarily on it (Økland et al 2001(Økland et al , Richard et al 2014. Movement away from holding pools therefore does not necessarily suggest a loss of territory, especially given that individuals move among pools during the spawning season (Taggart et al 2001), and a comparison to the movement exhibited by salmon in 2014 indicated no major differences in displacement.…”
Section: Discussionmentioning
confidence: 98%